2009
DOI: 10.1126/scisignal.2000405
|View full text |Cite
|
Sign up to set email alerts
|

The Kinesin Protein Kif7 Is a Critical Regulator of Gli Transcription Factors in Mammalian Hedgehog Signaling

Abstract: From insects to humans, the Hedgehog (Hh) signaling pathway has conserved roles in embryonic development and tissue homeostasis. However, it has been suggested that the lack of mammalian equivalents of Costal2 (Cos2) contributes to a divergence between the mechanism of Drosophila and mammalian Hh signal transduction. Here, we challenge this view by showing that the kinesin protein Kif7 is a critical regulator of Hh signaling in mice. Similar to Cos2, Kif7 physically interacted with Gli transcription factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
238
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(249 citation statements)
references
References 37 publications
(90 reference statements)
10
238
0
1
Order By: Relevance
“…Mice-The generation of Kif7-deficient mice was reported previously (11). Conditional Sufu-deficient mice (Col2a1-Cre; Sufu f/f ) were generated by crossing Col2a1-Cre mice expressing Cre recombinase under the control of type II collagen regulatory elements specific to chondrocytes with Sufu-floxed mice containing loxP sites flanking exons 4 -8 of Sufu.…”
Section: Methodsmentioning
confidence: 99%
“…Mice-The generation of Kif7-deficient mice was reported previously (11). Conditional Sufu-deficient mice (Col2a1-Cre; Sufu f/f ) were generated by crossing Col2a1-Cre mice expressing Cre recombinase under the control of type II collagen regulatory elements specific to chondrocytes with Sufu-floxed mice containing loxP sites flanking exons 4 -8 of Sufu.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, these observations suggest Shh-induced phosphorylation of Smo is both necessary and sufficient to recruit Evc/Evc2, and the binding between Smo and Evc/Evc2 is mediated by Smo C-tail and is likely dependent on primary cilia. Several studies have shown that Kif7, the mammalian homolog of Drosophila Cos2, is involved in Hh signaling [24][25][26][27]. In Drosophila, Hh-induced Smo phosphorylation and conformational change promotes Smo/Cos2 association [20,21].…”
Section: Hh-induced Phosphorylation Of Smo Promotes Its Binding To Evmentioning
confidence: 99%
“…Activated Fu regulates both the activator and repressor form of Ci, likely by phosphorylating Cos2 and Sufu [18,[20][21][22][23]. Both Sufu and the mammalian homolog of Cos2, Kif7, are involved in Hh signaling [24][25][26][27][28]. By contrast, the mammalian homolog of Fu is not required for Hh signaling during development [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…51 The latter is activated in many kinds of tumor cells, and recent evidence suggests that blocking aberrant Hh pathway signaling may be a promising therapeutic strategy for the treatment of several types of cancers. [52][53][54] These data suggest that the induction of KIF7 expression or activity may control human cancers effectively and, thus, may be used as a therapeutic tool.…”
Section: Kinesin-4 Familymentioning
confidence: 99%